The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1017/s026646230000965x
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Nerve Stimulation (TENS): A Technology Assessment

Abstract: The scientific evidence for clinical effectiveness of transcutaneous electrical nerve stimulation (TENS) for treatment of acute, chronic, and labor and delivery pain is assessed in this paper, and it is concluded that there is little evidence for other than a limited use of TENS. The utilization of TENS in Canadian hospitals and payments for TENS services are addressed. Some practicalities regarding the use and assessment of health technologies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 74 publications
(15 reference statements)
0
21
1
3
Order By: Relevance
“…These theories include inhibition of nociceptors, blockage of pain transmission in afferent nerves, sympathetic blockage, gate control theory and increase in release of endogen opiates (6). There is a conflicting evidence in the literature whether the TENS treatment is effective in reducing the pain caused by knee OA (7,8,15,16). In a panel organized in Philadelphia in 2001, 6 randomized controlled trials investigating the rehabilitation approaches to knee pain were reviewed systematically and the consensus report stated that despite the differences in those studies, TENS is useful in reducing pain and improving global assessment of patient (17).…”
Section: Discussionmentioning
confidence: 99%
“…These theories include inhibition of nociceptors, blockage of pain transmission in afferent nerves, sympathetic blockage, gate control theory and increase in release of endogen opiates (6). There is a conflicting evidence in the literature whether the TENS treatment is effective in reducing the pain caused by knee OA (7,8,15,16). In a panel organized in Philadelphia in 2001, 6 randomized controlled trials investigating the rehabilitation approaches to knee pain were reviewed systematically and the consensus report stated that despite the differences in those studies, TENS is useful in reducing pain and improving global assessment of patient (17).…”
Section: Discussionmentioning
confidence: 99%
“…The first systematic reviews on TENS were published in 1996 and they challenged the belief at the time that TENS was efficacious for acute and chronic pain (Carroll et al 1996, Reeve et al 1996 ( Table 1). Since then there has been a proliferation of systematic reviews, many using methodology of the Cochrane collaboration (Cochrane reviews).…”
Section: Evidence For the Effectiveness Of Tensmentioning
confidence: 99%
“…[43][44][45] However, a health technology assessment by Reeve et al 46 reported that TENS was demonstrated to be of bene t in only 12/20 randomized controlled trials (RCTs). A systematic review by Carroll et al 42 reported that TENS did not produce signi cant bene t when compared with placebo in 15/17 RCTs.…”
Section: Tens and Postoperative Painmentioning
confidence: 99%
“…Reeve et al reported that TENS was more effective than sham (n = 7) or no treatment (n = 2) in 9/20 RCTs. 46 McQuay and Moore stated that TENS was better than sham TENS, placebo pills, or inappropriate electrode placements in 10/24 RCTs. 56 Carroll et al reported that TENS provided better pain relief than sham or no treatment in 10/15 RCTs.…”
Section: Tens and Chronic Painmentioning
confidence: 99%